The Effect of Risk-Based Capital, Premium Income and Claim Expense on Profit of Reinsurance Companies in Indonesia - yustisia, natali; Batari, Afisyah Maudini (Universitas Mercu Buana, 2024)
This research aims to analyze the factors that can affect the profitability of reinsurance companies. These factors include risk based capital, premium income, and claim expense. The sample used is five reinsurance companies located in Indonesia that published financial statements in the 2012-2022 period with a purposive sampling method. The data analysis technique uses panel data and using the Eviews 12 software analysis tools software. The partial test results there was a significantly positive effect between the RBC variable and premium income on the reinsurance company's profit. However, variable claim expenses have a significant negative effect on reinsurance company profits. The result is an Adjusted R-squared value of 0.7706. This value can be interpreted that the independent variable can influence the dependent variable by 77.06 percent.